Constructal thermodynamics and its semantic ontology in autopoietic, digital, and computational architectural and urban space open systems - Mavromatidis, Lazaros (BioSystems, 2025)
This paper explores the intersections of constructal thermodynamics, and its semantic ontology within the context of autopoietic, digital and computational design in protocell inspired numerical architectural and urban narratives that are examined here as open systems. Constructal law is the thermodynamic theory based on the analysis of fluxes across the boundaries of an open system. Protocells, as dynamic, autopoietic and adaptive open finite size systems, serve in this paper as a compelling metaphor and design model for responsive and sustainable manmade architectural and urban environments. The ability of protocells to harness energy, minimize entropy, and adapt to environmental changes mirrors the principles of constructal thermodynamics, which govern the flow and distribution of resources in complex self-organizing information open systems in nature. By applying these principles to digital architecture, this study investigates how relational dynamics between spaces, materials, and functions can create adaptive designs that “go with the flow” of ecological and cultural systems. The research demonstrates using the Gouy-Stodola theorem as a variational principle, how protocell-inspired processes facilitate exergy-efficient designs, minimizing waste while maximizing resilience and flexibility. The present paper argues -through an applied case study- for a paradigm where protocell digital architecture serves not only as an ecological and material model but mainly as a spatial narrative driver, blending constructal and digital tools with cultural mythos. Finally, this paper exploring simultaneously the semantic complexity and ontology of such systems, in turn, connects these constructal driven digital designs to broader poly-narratives, embedding cultural, symbolic, philosophical and functional predicates into architectural forms.